A case series on ocular manifestations in Steven Johnson Syndrome and their varied presentation-Review of literature - Nagalakshmi Narayana-Swamy; Alhaj Farhath Tasneem (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Purpose: To discuss the possible ocular manifestations of Steven Johnson Syndrome and their management among different cases. Case: Patients aged 9, 15, 43years with Steven- Johnson Syndrome were reviewed for severity of ocular involvement. These patients presented with fever and involvement of skin, oral mucosa and conjunctiva. Case 1: Secondary to use of? Mefenamic acid, treated conservatively. Case 2: Secondary to use of carbamazepine, treated conservatively. Case 3: Secondary to use of cotrimoxazole, had adhesion of both upper and lower eyelids and part of lower bulbar conjunctiva to the lower eye lid.Treated by ocular surface reconstruction with mucus membrane graft. Conclusion: All the three patients with Steven Johnson Syndrome had varied manifestations requiring different treatment modailites.Appropriate intervention during acute ocular presentation and careful vigilance aids management.